Accelerating Renewable Energy: Analyzing United in Diversity (UID)’s Collaboration with Rocky Mountain Institute (RMI) in Indonesia's Pursuit of Sustainable Development Goal 7 - Variza, Baiq Nayla Adisty; Priadarsini, Ni Wayan Rainy (President University, 2024)
This manuscript explores how the Happy Energy Action Leadership (HEAL) program, launched by United in Diversity (UID) in collaboration with the Rocky Mountain Institute (RMI), supports Indonesia's efforts to achieve Sustainable Development Goal 7 (SDG 7). Indonesia faces significant challenges in transitioning from a fossil fuel-dominated energy landscape to renewable energy, including infrastructural, financial, and socio-economic barriers. Leveraging Multi-Level Governance (MLG) theory, the manuscript examines the collaborative dynamics among diverse stakeholders—local, national, and global—in the HEAL program. Key findings highlight the program’s focus on capacity-building, inclusive governance, and innovative financing as catalysts for a sustainable energy transition. While challenges such as workforce skill gaps and regulatory hurdles persist, the HEAL program presents scalable opportunities for accelerating renewable energy deployment. This study underscores the transformative potential of multi-stakeholder initiatives in bridging systemic gaps and aligning local actions with global sustainability goals.